Development of Cultural Vista Flipbooks to Improve Learning Outcomes of Natural and Social Sciences of Elementary School Students - Firgiawan, Tegar; Sunarso, Ali (FKIP Universitas Lampung, 2025)
This research aims to develop and test the effectiveness of the Flipbook Vista Culture learning media to improve the learning outcomes of natural and social sciences for fifth-grade elementary school students. This development is motivated by the ineffectiveness of conventional media and the complexity of natural and social science material that requires innovative and interactive media. This research uses the Research and Development (RnD) method of Borg & Gall, consisting of 8 stages. The research was conducted in two phases: development and trial. Initial data collection includes documentation, interviews, questionnaires, and observations. The instruments used in this study include pretest and posttest to test the effectiveness of the media and expert validation to test the feasibility of the developed media. Data analysis uses T-test and N Gain. The results of expert validation show that the Flipbook Vista Culture media is very feasible to use, with an average score of 87.5%. The effectiveness test shows a significant difference between pretest and posttest (0.000 < 0.05). The average N Gain improvement test reaches 0.55 with a moderate category. This proves that the Flipbook Vista Culture media is effective in helping students understand the material of Indonesia's cultural heritage. Based on the research results, the Flipbook Vista Culture media is recommended for use in elementary schools' natural and social science learning. This media is an interesting and innovative alternative compared to conventional media. The researcher recommends the Flipbook Vista Culture media be applied in learning, especially in fifth grade, to create meaningful learning. Keywords: flipbook, learning media, learning outcomes.